Market integrity as a mechanism for the protection of collective rights [La integridad del mercado como mecanismo de protección de los derechos colectivos] (2015)
This article analyzes the market as the space where the exchange of goods and services is jointly exercised for the satisfaction of basic and nonbasic needs, and where the fulfillment of rights from both, the economic freedom and the Economic, Social and Cultural Rights (ESCR) is also exercised. From this perspective, the analysis of the functioning of the market, as the institution that reaches the development of such exercises, can relate to collective rights associated with the healthy environment and the exercise of economic welfare. This welfare is represented in the freedom of choice of the economic activity itself and the consumer protection, with no other restrictions than the ones imposed by the development of the principles of equality, freedom of action and the preservation of life through the limitation of economic activities that generate disturbances to the environment.